Alloy disorder modulated electron transport at MgxZn1-xO/ZnO heterointerface - Aswin Vishnuradhan; Y. Kozuka; M. Uchida; J. Falson; A. Tsukazaki; M. Kawasaki (AIP Advances, 2017)
High-mobility electron systems in two dimensions have been the platform for realizing many fascinating quantum phenomena at low temperatures. Continuous demand to improve the sample quality has necessitated the investigations of various disorders influencing the quantum transport. Here, we study the effect of short-ranged alloy disorder on the scattering of two-dimensional electron system in MgxZn1-xO/ZnO. For this purpose, we employ a modified interface profile consisting of Mg0.01Zn0.99O/ZnO with a thin (2nm) MgxZn1-xO interlayer with x ranging from 0.005 to 0.4. This interlayer design allows us to investigate scattering mechanisms at a nearly constant carrier density as the interlayer is found not to significantly affect the carrier density but enhance alloy disorder. While the transport scattering time (τtr) shows a strong correlation with x, the quantum scattering time (τq) remains insensitive to x. The large variation in the τtr/τq ratio (from 16.2 to 1.5 corresponding to x from 0.005 to 0.4) implies a change in the dominant scattering mechanism from long range towards short range with increasing x. The insensitivity of τq on x indicates the scattering rate is not dominated by the alloy disorder. This implies that other scattering mechanisms, likely unintentional background impurities or remote surface disorders, are dominant in limiting τq, and therefore providing a prospect for pursuing ever higher levels in the quality of the two-dimensional electron system in MgxZn1-xO/ZnO system.